MULTICULTURALISM: THE IMPORTANCE OF RELIGIOUS MODERATION EDUCATION IN INDONESIA - Akhmad Khoiri; Wedi Samsudi; Munawaroh Munawaroh; Munif Shaleh (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2024)
Indonesia is a country with diversity which includes ethnicity, language, culture, social status and religion. This is one of the reasons why Indonesia is known as a multicultural country. With multiculturalism in Indonesia, it is necessary for people in Indonesia to have a moderate understanding of religion, this is usually called religious moderation. The aim of this research is to discuss religious moderation in uniting multicultural Indonesian society. The method used in this research is a qualitative method in the form of library research using a descriptive analysis approach. The results of this research show that a country that is nicknamed a multicultural society needs to have an understanding and awareness of the need for an attitude of respect for differences, diversity and ways of interacting with other people as best as possible without having to look at their background and origin. This is the reason why religious moderation education is needed by having an attitude of tolerance, respecting differences of opinion and recognizing the existence of other people, so that it can create a peaceful and harmonious Indonesian society.